(3GdQSGdI GdbOSjI GdWGgQI HTQM GdOQI GdaGNQIs - (3EHQGgje Hf MjOQ Hf CMeO GdcQOi GdMSjf BHGOis; (3fhQ GdOjf YHO GdQMef Hf CMeO Hf eMeO GdLGej GdfbTHfOj, GdLGej,J (B898 (3g` s ((3ejQ Ydi Hf ejQ SYjOG afOi NhbfOi s)
(3ChdgG (B:s
(3MeOkG dc jG ef GQJSe LeGdg ai eQGjG eXGgQ GdehLhOGJ hHYO jbhd GdYHO GdhGba HGdHGH GdNGVY deG QCjJ gPg GdOQI GdTQjaI GdaGNQI s
(3BNQgG (B:s
(3QCjJ ai GdefGe ai HYV GddjGdi cCfi SGcf ai GdbOS GdebOS hhGba HJdc GdehGba GdeDfS JeJ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs